EU-RUSSIA RELATIONS: UKRAINE CONFLICT, STRATEGIC DILEMMA’S AND COMPULSIONS - Prakash, Aditya (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The European Union (EU) and Russia have had complicated relations not only during the Cold War period (when Russia was part of the Soviet Union), but also from 1991 when the Soviet Union ceased to exist. Russia was the largest of the post-Soviet states and had inherited major aspects of the foreign policies of the Soviet Union. Whereas, the 1990’s witnessed Russia tilting towards the West, as Russia focused on rebuilding its economy and establish its influence in its near abroad i.e., Central Asia and the Balkans, its ambitions and claims on Ukraine as the most important region of Russia’s near abroad, from where Russia draws its cultural heritage and linkage never seemed to have diminished. While Ukraine evolved into an independent and democratic nation, adopting Western principles that helped to forge its own path towards progress and development, Russia with its pursuit of a regional hegemon has evolved into an authoritarian regime under its longest serving leaders in the modern times, i.e., Vladimir Putin. Russia changed the course of its policies and ambitions in the post-Cold War Phase and this culminated into the present Russia-Ukraine conflict, which has place the European Union an arch supporter of Ukraine against Russia. This paper tries to understand the complex, dynamic and evolving relations between the EU and Russia, while there is an unprecedented devastation caused by the Russia-Ukraine conflict. The paper also tries to examine the geopolitical compulsions and the strategic dilemmas that have shaped the EU-Russia relations because of the conflict. A special focus will be on issues that strongly affect EU and Russia at present i.e., economy, security and political aspects between the two parties. The conflict has unravelled broader strategic tensions in the region, from the need to maintain security to avoiding conflicts that may destabilize regional economies and from evolving policy changes on Russia by the EU to some EU members having individual relations with Russia. These issues will be analysed to gain insights into the ongoing strategic interplay, outlining the limitations and future pathways for EU-Russia relations amidst the enduring geo-political crisis in the form of Russia-Ukraine conflict.